The Analysis Of Purchase Intention Antecedents Of Café Visitors In Batam - Reni, Agus Tamrin; Ariyanto, Hepy Hefri; Barata, Dion Dewa (Jurnal Ilmu Sosial Mamangan, 2025)
This study examined the influence of menu attractiveness, menu informative aspects, and the risk of COVID-19 on perceived food ordering convenience, as well as the influence of perceived food ordering convenience on purchase intentions. This study's sample consisted of 375 respondents who had frequented and made purchases at cafés in Batam. The questionnaire method was utilized to collect data for this study. This study employs the Structural Equation Model with the Partial Least Squares method and the SmartPLS 3.2.8 software for its analysis. 1) Menu attractiveness has a significant impact on perceived convenience in ordering food; 2) Menu informative aspect has a significant impact on perceived convenience in ordering food; 3) Covid-19 risk has a significant impact on perceived convenience in ordering food; and 4) The convenience felt in ordering food has a significant impact on purchase intention.